Real-World Prevalence of Direct Oral Anticoagulant Off-Label Doses in Atrial Fibrillation: An Epidemiological Meta-Analysis - Nan-Nan Shen; Nan-Nan Shen; Chi Zhang; Chi Zhang; Ying Hang; Zheng Li; Ling-Cong Kong; Na Wang; Jia-Liang Wang; Zhi-Chun Gu; Zhi-Chun Gu; Zhi-Chun Gu (Frontiers Media S.A., 2021)
Background: The use of direct oral anticoagulant (DOAC) off-label doses in atrial fibrillation (AF) patients may result in poor clinical outcomes. However, the true prevalence remains scarce. This study aims at estimating the prevalence of DOAC off-label doses in AF patients.Methods: Databases of MEDLINE, EMBASE, and COCHRANE were searched from inception through February 2020 for real-world studies that reported the off-label definition and prevalence data of AF patients using DOACs. The primacy outcomes were the overall prevalence of DOAC off-label doses and the corresponding underdose and overdose. The random-effects model was used for data synthesis. Variations on individual DOAC and different regions were examined by subgroup analyses.Results: A total of 23 studies involving 162,474 AF patients were finally included. The overall prevalence of DOAC off-label doses was 24% (95% CI, 19-28%), with 18% for dabigatran, 27% for rivaroxaban, 24% for apixaban, and 26% for edoxaban. The prevalence of underdosed DOACs was 20% (95% CI, 16-24%) with significant difference among individual anticoagulants (13% for dabigatran, 22% for rivaroxaban, 22% for apixaban, and 18% for edoxaban; Pinteraction=0.02). The prevalence of overdosed DOACs was 5% (95% CI, 3-7%), with the lowest prevalence observed in apixaban (2%). Subgroup analyses by regions demonstrated that the prevalence of DOAC off-label doses was higher in Asia (32%) than in North America (14%) and in Europe (22%), with underdose being predominant. Regardless of different regions, the prevalence of overdose was relatively low (4-6%).Conclusion: This study provides an estimation of DOAC off-label doses in the real-world setting. The prevalence rate of DOAC off-label doses in AF patients was relatively high, with underdose being predominant. Clinicians in Asia preferred to prescribe underdose of DOACs to AF patients. More evidence about the appropriateness of DOAC off-label doses in AF patients is urgently needed. Education programs concerning the appropriate prescription of DOACs within the drug labels and accepted guidelines are necessary to DOAC prescribers to ensure the safety and effectiveness of anticoagulation therapy for patients with AF.